2015
DOI: 10.1017/jmo.2015.50
|View full text |Cite
|
Sign up to set email alerts
|

Collectivism-oriented human resource management and innovation performance: An examination of team reflexivity and team psychological safety

Abstract: This article investigated how collectivism-oriented human resource management can influence on innovation performance through team reflexivity and team psychological safety. Using a sample of 200 research-oriented teams in Chinese universities, the empirical results clearly indicate that collectivism-oriented human resource management is beneficial to teams’ innovation performance. The results of the mediating model show how team reflexivity and team psychological safety mediate the relationship between collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 73 publications
1
20
0
Order By: Relevance
“…More specifically, this research has shown how diverse and complementary management team resources are linked to ambidexterity and better firm performance (Fu et al, 2008 ; Liu et al, 2009 ; Li et al, 2016 ; Li and Cui, 2018 ), or that innovation is spurred by cognitive task conflict (He et al, 2014 ), and such conflicts can be handled at an optimal level so as not to turn into counterproductive relationship conflicts (Farh et al, 2010 ). Just as in all other contexts, psychological safety and trust mediate team performance through voice (Wang et al, 2010 ) and empowerment (Chen and Tjosvold, 2012 ; Hempel et al, 2012 ; Chen S. et al, 2015 ; Dai et al, 2016 ), in such a way that knowledge is shared and not concealed (Ma et al, 2014 ; Huo et al, 2016 ).…”
Section: General Theoretical Overview: Teams Vs Organizationsmentioning
confidence: 99%
“…More specifically, this research has shown how diverse and complementary management team resources are linked to ambidexterity and better firm performance (Fu et al, 2008 ; Liu et al, 2009 ; Li et al, 2016 ; Li and Cui, 2018 ), or that innovation is spurred by cognitive task conflict (He et al, 2014 ), and such conflicts can be handled at an optimal level so as not to turn into counterproductive relationship conflicts (Farh et al, 2010 ). Just as in all other contexts, psychological safety and trust mediate team performance through voice (Wang et al, 2010 ) and empowerment (Chen and Tjosvold, 2012 ; Hempel et al, 2012 ; Chen S. et al, 2015 ; Dai et al, 2016 ), in such a way that knowledge is shared and not concealed (Ma et al, 2014 ; Huo et al, 2016 ).…”
Section: General Theoretical Overview: Teams Vs Organizationsmentioning
confidence: 99%
“…Scholars identify differences across societies marked by collectivism versus individualism with regard to many facets of the organization. For example, research has examined the impact of collectivism on recruitment and selection (Sinha, 1997; Herrera, Duncan, Green, Ree, & Skaggs, 2011; Manroop, Boekhorst, & Harrison, 2013; Cooke, Veen, & Wood, 2016), promotion (Aycan, 2005; Sekiguchi, 2006), performance appraisals (Amba-Rao, Petrik, Gupta, & Von der Embse, 2000; Aycan, 2005; Varma, Pichler, & Srinivas, 2005; Chiang & Birtch, 2010, 2011; Yahiaoui, 2014; Hossain, Abdullah, & Farhana, 2015), compensation (Gomez-Mejia & Welbourne, 1991; Luis & Mejia, 1991; Schuler & Rogovsky, 1998; Aycan, Kanungo, & Sinha, 1999; Chiang, 2005; Yeganeh & Su, 2011; Yahiaoui, 2014), teamwork (Chen, Zhang, Zhang, & Xu, 2016), and CEO or top manager pay (Tosi & Greckhamer, 2004; Pudelko, 2005). Although institutional and in-group collectivism are rarely studied as separate dimensions, developing a better understanding of the notion of collectivism remains important for determining successful management practices across societies.…”
Section: Globe Cross-cultural Studies and Management Practicesmentioning
confidence: 99%
“…Studies have shown that TPS has a positive effect on information sharing (Zhang et al, 2010;Chen et al, 2016). When a stranger joins a team discussion, this will cause discomfort and embarrassment, and consequently, members will deliberately retain, conceal or falsify personal information related to the task, or even strategically lie about it (Steinel, Utz, Koning, 2010).…”
Section: Tps As a Moderatormentioning
confidence: 99%